Developing Teaching Aids For The Arabic Language Book In Reading Skill On PowerPoint Android - Ahmad Hidayatullah Zarkasyi; Siti Anne Barkah Nur Fauziah; Gita Hanina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The Arabic language is difficult for students, especially for reading Arabic texts. This study aims to develop and produce teaching aids for the Arabic Language book in reading skills on PowerPoint Android programs for the ninth-grade preparatory school and show the effectiveness of its implementation using the qualitative and quantitative approaches. Data collection using tests and student observations. The researcher used Borg and Gall’s proposed research and development (RD). The effectiveness of this method is obtained from the development of students’ Arabic text reading skills visible after using the Android PowerPoint. The result indicates progress in their language ability, basically in reading skills. These teaching aids are attractive and exciting PowerPoint Android programs and help students learn Arabic. Especially reading Arabic, appropriate material, exercises, and teaching methods are chosen to have an essential role in the education process, and it is the most excellent helper in facilitating and clarifying problems in lessons and paying attention to the needs of students and teachers. Hence, the researcher saw that the developed methods are practical, easy, and exciting in the educational process.